National Action Plan on Antimicrobial Resistance (AMR) 2016-2020 and relevant activities in Japan - Ohmagari, Norio (Global Health & Medicine, 2019)
Antimicrobial-resistant bacteria that are spreading all over the world have caused significant problems. While these problems are becoming bigger, the development of new antimicrobials has remained stagnant, and some essential antimicrobials for treatment may be depleted in the near future. This is a significant problem that may jeopardize the sustainability of healthcare itself. In Japan, the National Action Plan on Antimicrobial Resistance was established in April 2016. Based on the five strategic objectives set out in the World Health Organization's Global Action Plan on Antimicrobial Resistance, and by adding a 6th objective of international cooperation as a Japanese unique goal, the goals, strategies and specific actions of each of these six fields are presented. This Action Plan is significantly characterized by setting numerical targets as a performance index to be achieved by 2020.